ZAKAT, KHARĀJ, ’USHR, AND JIZYA AS THE INSTRUMENTS OF ISLAMIC PUBLIC FINANCE: A CONTEMPORARY STUDY - Nafis Irkhami (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
The aim of this article is to find out the conceptual construction of zakat (alms) and taxes in Islamic public finances. Its significance is to propose an alternative for Islamic public policy. It also means to enhance literature on Islamic public finance. This qualitative study is an explorative-analysis, which is intended to unravel key concepts of the classical scholar thought, both from primary and secondary sources. It clarifies various charges in the institution of zakat as like taxation in general economics. This study finds that the ultimate goal of Islamic political economy is the fulfillment of the basic needs of every citizen. Thus, its concepts and approaches are different from conventional economics, which promotes the aggregate economic growth and ignores the well-being of individuals. The government has the competence of public policy to collect something from the public according to its consideration, for example, jizya and kharāj. Regarding fair distribution, the government also has an obligation to take public finance policies (allocation of state expenditures, including zakat to the rightful parties).==============================================================================================Zakat, Kharāj, ’Ushr, and Jizya sebagai Instrumen Keuangan Publik Islam: Suatu Kajian Kontemporer. Tujuan penulisan artikel ini adalah untuk memahami kerangka konseptual mengenai zakat dan pajak dalam keuangan publik Islam. Signifikansinya adalah untuk mengusulkan alternatif kebijakan publik Islam. Dengan demikian studi ini juga dimaksudkan untuk melengkapi kajian literatur keuangan publik Islam. Studi kualitatif ini bersifat eksploratif-analisis, yakni dimaksudkan untuk mengungkap konsep-konsep kunci dari pemikiran klasik, baik dari sumber primer dan sekunder. Kajian ini mengklarifikasi berbagai justifikasi negatif terhadap institusi zakat, sebagaimana perpajakan dalam ekonomi umum. Studi ini menemukan bahwa tujuan akhir dari ekonomi politik Islam adalah pemenuhan kebutuhan dasar setiap warga negara. Dengan demikian, konsep dan pendekatannya berbeda dari ekonomi konvensional yang mempromosikan pertumbuhan ekonomi secara makro dengan mengesampingkan kesejahteraan individual. Pemerintah memiliki kompetensi kebijakan publik untuk menarik pemasukan publik sesuai pertimbangannya, misalnya dengan jizyah dan kharāj. Terkait dengan pemerataan distribusi, pemerintah juga memiliki kewajiban untuk mengambil kebijakan keuangan publik (alokasi pengeluaran negara, termasuk zakat, kepada pihak-pihak yang berhak).